Prevalance of stress and its risk factors among medical students - B., Rock; R., Ronald; T., Elamparithi; S., Zakeena; M., Susin; R., Sundri; J., Vivek; K., Naveen (International Journal Of Community Medicine And Public Health, 2017)
Background: Studying medicine is stressful. Stress may cause serious health problems and affects their professional life. Hence establishing a database on the extent of the problem will help in the planning of measures to reduce stress. The aim of the study was to determine the prevalence and risk factors of stress among the medical students. Methods: Cross-sectional study was done using 40 item medical student stressor questionnaire (MSSQ) to evaluate the level of stress and the stressors and hence finding the factors associated with it. Data were analysed using EPI INFO. Results: Of the medical students who were administered questionnaire, 250 (83%) participated in the study. About 17.2% are from Tamil medium. 37.2% were first child in the family. 64.4% and 57.6% have responded that 6-8hrs sleep needed and the actual sleeping hours respectively. About 74%, 75.2%, 62.8% and 56.4% have less focus, less energy and motivation, negative mood and poor academic performance due to decreased sleep. Academic and group related activities contribute to about 29.2%, 20.8% of the total stress respectively. Conclusions: The prevalence of stress among medical students is moderate to high. The second and final year students are having high stress levels. Academic and group related activities were the major stressors among medical students. Year of study and being the first doctor in the family were the best predictors of a medical student’s stress level.